Peran Pembelajaran Aktif dalam Meningkatkan Pemahaman Materi PAI - Istifada Lailatil Musyarrofah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character and morals, especially amidst the increasingly complex flow of globalization. In the era of fast and diverse information, the method of delivering PAI material needs to be adjusted so that it remains relevant and effective for the younger generation. PAI is not just a theoretical teaching, but also a place to instill moral and ethical values ​​contained in Islamic teachings. One approach that is increasingly popular in education today is active learning. Active learning emphasizes direct student participation in the learning process. In this approach, students not only act as recipients of information, but also as explorers, discussants, and implementers of the material being studied. This involvement is important because it can help students understand religious concepts more deeply and critically, and connect them to their daily experiences and life contexts.